2021
DOI: 10.1029/2021jf006153
|View full text |Cite
|
Sign up to set email alerts
|

Does Load‐Induced Shallow Subsidence Inhibit Delta Growth?

Abstract: Despite a reduction in the sediment flux from continents to oceans on a global scale (Syvitski et al., 2005), many river deltas have continued to grow in recent decades (Nienhuis et al., 2020). However, it is unlikely that this growth can be sustained under future scenarios of relative sea-level rise (RSLR), in part due to the commonly high subsidence rates in deltas. RSLR is a major threat to the sustainability of these ecologically, economically, and culturally significant regions (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 62 publications
(152 reference statements)
0
13
0
Order By: Relevance
“…We designed the reduced‐complexity modeling approach undertaken in this study to exclusively test the impact of future SLR on river‐dominated delta landscapes. As a result, we did not consider many physical processes such as wind (e.g., Ortiz et al., 2017), waves (e.g., Anthony, 2015), vegetation (e.g., Lauzon & Murray, 2018; Piliouras et al., 2017), tides (e.g., Galloway, 1975; Sassi et al., 2012), subsidence (e.g., Chamberlain et al., 2021; Zoccarato et al., 2018), and variable discharge (e.g., Gao et al., 2019; Miller et al., 2019; Shaw & Mohrig, 2014), although their presence, absence, and relative magnitudes are known to influence delta evolution. However, we do not believe that all of these additional forcings would significantly change the results found here; Van De Lageweg and Slangen (2017) simulated delta evolution over centennial timescales with different forcing and SLR conditions, and found river, tidal, and wave‐dominated deltas all responded similarly to SLR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We designed the reduced‐complexity modeling approach undertaken in this study to exclusively test the impact of future SLR on river‐dominated delta landscapes. As a result, we did not consider many physical processes such as wind (e.g., Ortiz et al., 2017), waves (e.g., Anthony, 2015), vegetation (e.g., Lauzon & Murray, 2018; Piliouras et al., 2017), tides (e.g., Galloway, 1975; Sassi et al., 2012), subsidence (e.g., Chamberlain et al., 2021; Zoccarato et al., 2018), and variable discharge (e.g., Gao et al., 2019; Miller et al., 2019; Shaw & Mohrig, 2014), although their presence, absence, and relative magnitudes are known to influence delta evolution. However, we do not believe that all of these additional forcings would significantly change the results found here; Van De Lageweg and Slangen (2017) simulated delta evolution over centennial timescales with different forcing and SLR conditions, and found river, tidal, and wave‐dominated deltas all responded similarly to SLR.…”
Section: Discussionmentioning
confidence: 99%
“…Trends of increasing connectivity as the rate of SLR increased in the "abrupt" and "gradual" scenarios, suggest that the shallow subsurface of natural river deltas in the future will become more connected as sea levels rise. The shallow subsurface is also susceptible to subsidence due to compaction (e.g., Keogh et al, 2021;Teatini et al, 2011;Törnqvist et al, 2008;Van Asselen et al, 2011), a process not considered in this work, but one which can impact delta growth and evolution (Chamberlain et al, 2021;Zoccarato et al, 2018).…”
Section: Subsurface Connectivity Of Shallow Deltaic Stratigraphymentioning
confidence: 99%
“…Notwithstanding the overall modest subsidence rates at the superstation site, this may change in the near future due to the Mid‐Barataria Sediment Diversion that aims to build and maintain deltaic (wet) land in the area surrounding the superstation (Coastal Protection and Restoration Authority of Louisiana, 2017). When implemented, this river diversion will bring a significant increase in clastic sediment, likely accelerating shallow compaction (e.g., Chamberlain et al., 2021). Our data provide a valuable pre‐diversion baseline to assess the impacts of the Mid‐Barataria Sediment Diversion with regard to subsidence.…”
Section: Synthesis and Implicationsmentioning
confidence: 99%
“…While this may not presently be the case at the superstation, it is well documented that Holocene sediment compaction dominates the total present‐day subsidence in most of coastal Louisiana (e.g., Chamberlain et al., 2021; Jankowski et al., 2017; Karegar et al., 2015; Keogh et al., 2021; Meckel et al., 2006; Penland & Ramsey, 1990; Törnqvist et al., 2008). Previously buried (Pleistocene) sediments do not significantly decompact with unloading (Chapman, 1983).…”
Section: Synthesis and Implicationsmentioning
confidence: 99%
“…Furthermore, Day et al (2011) found that soil strength is higher in marshes with riverine MM input compared to marshes with high OM content that lack riverine input. However, MM-dominated deltaic muds are also highly compressible (e.g., Fisk et al, 1954;Minderhoud et al, 2018;Zoccarato et al, 2018) and may be at least as compressible as organic-rich sediments in some cases (e.g., Chamberlain et al, 2021).…”
mentioning
confidence: 99%